40Ar/39Ar Geochronological Constraints on the Age Progression Along the Juan Fernández Ridge, SE Pacific - Lara, Luis E.; Reyes, Javier; Jicha, Brian R.; Díaz-Naveas, Juan (Frontiers in Earth Science, 2018)
Juan Fernández Ridge (JFR) is a ca. 800 km long volcanic chain composed by seamounts, guyots and oceanic islands in the SE Pacific. JFR is thought to be related to a deep mantle plume and usually scores high in the hotspots catalogs (e.g., Anderson, 2005; Jackson et al., 2017). High 3He/4He in Robinson Crusoe is probably the most undoubted feature of lower mantle involvement. However, one of the most convincing pieces of evidence for a source rooted deep in the mantle is the age progression along a volcanic chain, which is poorly constrained for JFR. In fact, some scarce K-Ar dates in Alejandro Selkirk and Robinson Crusoe islands, and a total fusion age for O’Higgins Guyot published more than 20 years ago, is the only evidence available for such a hypothesis in previous works. Here we integrate recently published 40Ar/39Ar ages and 17 new results on groundmass step heating experiments from rocks corresponding to the late shield stage (O’Higgins Guyot: 8.4 Ma; Alpha Guyot: 4.6; Robinson Crusoe Island: 3.7 Ma; Alejandro Selkirk Island: 0.83 Ma; Friday Seamount: 0.62 Ma) to document a solid age progression which yields a long-term absolute velocity of ca. 81 mm/yr- for the Nazca Plate. This value is much higher than the velocity prescribed by plate tectonic models that assume fixed hotspots, and still somewhat higher than models that take into account hotspot drift, indicating that the Juan Fernández hotspot is moving ca. 2 cm/yr towards East Pacific Rise. Present hotspot would be ca. 20 km west of Domingo Seamount. Merging geochronological data with our current understanding of the mantle sources and magmatic evolution, we provide a case for a hotspot possibly rooted in a weak primary plume, and discuss some causes and consequences of that.